(untitled) (Journal of Economic Research & Business Administration, 2016)
In this article thoughts and ideas of the scientists-thinkers of the Islamic world in the Middle Ages who have influenced formation and formation of history of economic doctrines are considered. Medieval Islamic philosophy as well as in Europe, originally I developed within divinity. Her greatest blossoming falls on the XI–XII centuries, but also later, despite gradual strengthening in Islamic divinity of dogmatism and mysticism, in her deep thinkers meet. The native of Tunisia, the philosopher and the historian Valieddin Abdarrakhman ibn Haldun (1332 – 1406) who has put forward the first in Muslim philosophy theory of development of society in which the big place has been allocated to economic problems was one of them. With transition to a civilization stage, according to the theory Ibn-Halduna, appears also the state meaning transition from equality and breeding democracy to the relations of an inequality and domination.